COURSE OF THREATENED ABORTION IN CHRONIC GASTRITIS OF DIFFERENT TYPES - Zherebak, Nadiia; Gnatko, Olena (The Ukrainian Scientific Medical Youth Journal, 2020)
Abortion is one of the most important medical and social problems in the world. Functional and morphological sexual changes associated with the normal fetal growth and development during physiological pregnancy involve other maternal organs and systems to varying extent, and provide changes in metabolic and homeostasis processes in new conditions to preserve pregnancy. Gastrointestinal motility disorders can be a leading pathogenetic factor that contributes to the development of many common gastrointestinal disorders. During pregnancy, decreased intestinal motility may play a pathogenetic role in pregnancy as a factor leading to decreased intestinal motor and evacuation function and negative impact on pregnancy. The aim of the study was to determine the clinical course of threatened abortion in early gestation in women with different types of chronic gastritis to optimize the management of pregnancy. 67 pregnant women with threatened abortion at 8-12 weeks of gestation were examined. They were divided into 2 groups: Group 1 - 35(52.2%) women with chronic gastritis and Group 2 - 32(47.8%) patients without gastritis. At the beginning of pregnancy, all women with chronic gastritis had remission. A comparative assessment of the frequency and severity of manifestations of this complication at an early stage on the leading clinical signs: pain, bleeding, retrochorial hematoma in combination with major (vomiting, constipation) motor-evacuation function of the gastrointestinal tract in different types of gastritis was performed to determine the role of motor and evacuation function of the gastrointestinal tract in the development of the risk of abortion in pregnant women with gastritis. The type of gastritis was confirmed according to the level of basal secretion of serum gastrin 17 (G-17) with the stimulation test. The obtained results were processed by mathematical and statistical analysis methods with determination of average values ​​(M±m), Student’s test and confidence index (statistically significant difference was considered as р˂0,05). Results. All women were of reproductive age, the average age of pregnant women in groups had no statistical difference. Analysis of the frequency of clinical manifestations of threatened abortion showed that 35(100%) had pain symptoms, 30(85.7%) had bloody discharge and 10(28.6%) had retrochorial hematoma in Group 1, and 32(100%), 12(37.5%), 5(15.6%), respectively, in Group 2. Assessment of the intensity of threatened abortion symptoms showed that moderate pain was most often observed in all types of gastritis. Mild symptoms were in normoacidic women of Group 1 (11.4%) and Group 2 (9.4%). 2.9% of hyperacidic pregnant women in Group 1 and 3.1% of hypoacidic women in Group 2 reported severe pain. Analysis of the bleeding nature and intensity showed that women in Group 1 with all types of gastritis had spotting: 11.4% of hyperacidic type, 20.0% of normoacidic type and 11.4% of hypoacidic type. Moderate bleeding was observed in different types of chronic gastritis in pregnant women of Group 1 and various acidic conditions in Group 2. Moderate bleeding was significantly more common (7.4-fold) in hyperacidic pregnant women of Group 1 compared with Group 2. Retrochorial hematomas were registered in Group 1 as 14.3% in hyperacidic patients, 5.7% in normoacidic patients and 8.6% in hypoacidic women. Retrochorial hematomas were 2.5-fold more common in hyperacidic gastritis compared with normoacidic and 1.7-fold more common in hypoacidic gastritis. Estimation of the frequency of combined clinical manifestations of functional gastrointestinal diseases in pregnant women with threatened abortion showed that the manifestations of threatened abortion only were observed in 65.6% without gastritis, and only in 5.7% with gastritis. Different variants of combined clinical manifestations of gastrointestinal functional disorders and threatened abortion significantly prevailed in women with chronic gastritis: threatened abortion and vomiting were 3-fold more common, threatened abortion and vomiting and constipation - 4.3-fold, threatened abortion and constipation - 1.6-fold. The combination of threatened abortion and vomiting with various acidity was most common in hyperacidic condition (2,7-fold more common in Group 1 than in Group 2). The variant of the combination of threatened abortion, vomiting and constipation in hyperacid state was 3.6 times more common in Group 1 than in Group 2. Threatened abortion with constipation was registered in 17.1% of women in Group 1 with hyperacidity, which was 2.7 times more often than in women of Group 2. The most common clinical manifestations of threatened abortion and functional gastrointestinal disorders were seen in pregnant women with chronic hyperacidic gastritis. Conclusion. Dysfunction of the motor and evacuation gastrointestinal activity is important in the clinical course of threatened abortion based on the type of chronic gastritis, mediated by the different acid-producing gastric function which indicates the need to optimize treatment of threatened abortion in pregnant women with different types of chronic gastritis.